Biological tumor markers associated with local control after primary radiotherapy in laryngeal cancer: A systematic review. (23rd April 2020) - Noordhuis, Maartje G.; Kop, Emiel A.; van der Vegt, Bert; Langendijk, Johannes A.; van der Laan, Bernard F. A. M.; Schuuring, Ed; de Bock, Geertruida H.
Abstract: Background: The choice of treatment in laryngeal cancer is mainly based on tumor stage, post‐treatment morbidity and quality of life. Biological tumor markers might also be of potential clinical relevance. Objective of the review: The aim was to systematically review the value of published biological tumor markers to predict local control in laryngeal cancer patients treated with definitive radiotherapy. Type of Review: Systematic review. Search strategy: PubMed, Embase, Cochrane Library. Evaluation Method: A literature search was performed using multiple terms for laryngeal cancer, radiotherapy, biological markers, detection methods and local control or survival. Studies regarding the relation between biological tumor markers and local control or survival in laryngeal cancer patients primarily treated with radiotherapy were included. Markers were clustered on biological function. Quality of all studies was assessed. Study selection, data extraction and quality assessment was performed by two independent reviewers. Results: A total of 52 studies out of 618 manuscripts, concerning 118 markers, were included. EGFR and P53 showed consistent evidence for not being predictive of local control after primary radiotherapy, whereas proliferation markers (ie high Ki‐67 expression) showed some, but no consistent, evidence for being predictive of better local control. Other clusters of markers (markers involved in angiogenesis and hypoxia, apoptosis markers, cell cycle, COX‐2 and DNA characteristics) showed no consistent evidence towards being predictors of local control after primary radiotherapy. Conclusions: Cell proliferation could be of potential interest for predicting local control after primary radiotherapy in laryngeal cancer patients, whereas EGFR and p53 are not predictive in contrast to some previous analyses. Large diversity in research methods is found between studies, which results in contradictory outcomes. Future studies need to be more standardised and well described according to the REMARK criteria in order to have better insight into which biomarkers can be used as predictors of local control after primary radiotherapy.